Transient stability analysis of the Iraqi National Super Grid System (INSGS) / Holison Emang Wan - Wan, Holison Emang (2009)
The growth in population has become an increase source for a larger power system. Many power systems are newly built and existing power systems are expanded to meet the growing demand of electricity. Due to the continuous expansion of the power system and the growth in electricity demand, new and larger problems are expected to be encountered. Therefore, methods to solve these new encountered problems as well as the existing problems more efficiently and quickly are needed to ensure continuous supply of electricity to consumers.